Financial Feasibility of Sugar-Free Medium-Scale Dry Fruit Production: a Hypothetical Business Model - Martirosyan, A. E.; Markosyan, D. Z. (ՀԱԱՀ հիմնադրամ)
This article studies the financial feasibility of a medium-scale business model operating in dry fruit processing sector, which can also provide an economic insight for those who want to transform the substantial fruit processing into a well-performing business enterprise. To evaluate how viable the business is, the main capital budgeting techniques have been applied. The financial model shows that the business is profitable with positive net present value, profitability index equal to 1.20, payback period of 4.3 years and internal rate of return (IRR) greater than the weighted average cost of capital.
Keywords: Agricultural Economics and Agribusiness